Product traceability in manufacturing industries: Business case and pilot project. - Gonnagar, Anand Subhashchandra (2020)
Innovation is increasing rapidly in every sector of the industry. This improvement and development are imperative to industries. Some are up-to-date, and others are improving. We are already witnessing the era of technology-dependent industry, where technology plays a key role in the manufacturing processes. Disruptive technologies are changing the way enterprises operate. It is essential for the industries which are focused on delivering fast and reliable service to the clients. As the technology and innovation are increasing, they could help the ceramic industry for the options presently available in interrelated technology, which are already impacting the industrial development in Industry 4.0 During previous industrialization eras there have been many improvements in different industrial sectors, which have led to rapid growth universally across industries. The present research included the review of approaches towards the ceramic traceability industry. This thesis presents a discussion on traceability of products in the ceramic industry by observing the production process. There are many stages of the production process where the materials and products are difficult to track, However, industries are concerned about the quantity and number of products produced that will meet the expectations at the end. It is challenging for the enterprises to manage, organize and trace the products throughout the manufacturing process, from raw material till final packaging. Radio Frequency Identification (RFID) systems are a common and useful tool in manufacturing, supply chain management, and retail inventory control. Optical barcodes, another universal automatic identification system, have been a familiar packaging feature on consumer items for years. Due to advances in silicon manufacturing technology, RFID costs have dropped significantly. Soon, low-cost RFID “electronic product codes” or “smart-labels” may be a practical replacement for optical barcodes on consumer items. Unfortunately, the universal deployment of RFID devices in consumer items may pose new security and privacy risks not present in closed manufacturing environments. This thesis presents an introduction to RFID technology, identifies several potential threats to security and privacy, and offers several practical proposals for efficient security mechanisms.